FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KEKURANGAN ENERGI KRONIK (KEK) PADA IBU HAMIL DI PUSKESMAS TINGGI RAJA KABUPATEN ASAHAN - Annisa Febriana Siregar (Jurnal Penelitian Kesmasy, 2021)
Pregnant woman who suffered nutrition has risk delivered babies with low birth weight. Chronic energy deficiency cause of major problem for pregnant women. This study aims to see the factors related to occurrence of cronic energy deficiency on pregnant woman in Puskesmas Tinggi Raja, Kab. Asahan. This research method is an observational description with cross-sectional design. The sample is pregnant woman in Puskesmas Tinggi Raja, Kab. Asahan. The sample is 50 people. The data analysis used in this study was the Chi-Square test (95% CI) From the result of this research showed that 83,3% of pregnant woman under twenty years old, with occurrence of cronic energy deficiency. 83,3% mothers education mostly elementary school graduates and junior high school graduates. The majority of mothers as a house wife (85,2%) and their in come less than UMR per month (82,8%). The level of knowledge of mothers on chronic energy deficiency is still lacking (79,2%). The conclusion factors related to occurrence of cronic energy deficiency